Comparative Analyses of Clinical Features, Histopathology, and CD123 Immunohistochemistry of Oral Lupus Erythematosus, Lichen Planus, and Other Lichenoid Lesions - Kumutnart Chanprapaph (2022)
Background: Oral lupus erythematosus (OLE) and oral lichen planus (OLP) are among the common causes of oral lichenoid lesions (OLLs). The differential diagnosis among causes of OLLs, particularly between OLE and OLP, is challenging as they have significant clinical and histopathological overlap. Objectives: To compare and summarize the clinical, histopathological, and direct immunofluorescence (DIF) findings between OLE, OLP, and other OLLs and to explore the diagnostic value of CD123 immunohistochemistry. Methods: A retrospective study on patients with OLE, OLP, and other OLLs was performed between January 2014 and December 2019. The baseline characteristics, the clinical, histopathological, and DIF features, as well as CD123 immunohistochemistry for plasmacytoid dendritic cells (PDCs) were statistically analyzed and compared between groups. Results: Of 70 patients, 12 had OLE, 39 had OLP, and 19 had other OLLs. Oral erosions/ulcers were the most common findings in all three groups. Red macules, telangiectases, and discoid plaques were more common in OLE patients, while OLP cases were typified by reticulated patches (p < 0.05). Additionally, white patches were found more often in other OLLs than in both OLE and OLP (p = 0.002). Histologically, mucosal atrophy, basal vacuolization, and perivascular infiltrate were observed in OLE, whereas OLP specimens possessed mucosal hyperplasia, hypergranulosis, and compact orthokeratosis (p < 0.05). Mucosal spongiosis was a histologic feature that favored other OLLs over OLE and OLP (p < 0.001). Data on DIF were nonspecific for all three conditions. For immunohistochemical staining, the median number of total CD123+ PDCs was observed to be higher in OLE than OLP in the mucosal-submucosal junction (MSJ) (p = 0.021), the superficial perivascular area (p = 0.026), and the superficial and deep perivascular areas (p = 0.001). Likewise, PDCs in clusters ≥2+ were seen in significantly higher numbers on OLE than OLP along the MSJ (p = 0.002), the superficial perivascular area (p < 0.001), as well as the superficial and deep perivascular areas (p = 0.011). CD123+ PDCs were found to be significantly more numerous in both OLE and OLP than other OLLs in all of the abovementioned areas (all p < 0.05). Conclusion: While there are some differences in the clinicopathological features between OLE, OLP, as well as other OLLs, a significant overlap remains. The quantity and distribution pattern of CD123 immunohistochemical staining has a diagnostic implication in differentiating OLE from OLP and other OLLs.